Biological Impact and Enzyme Activities of Spodoptera litura (Lepidoptera: Noctuidae) in Response to Synergistic Action of Matrine and Beauveria brongniartii - Wu, Jianhui; Li, Jiaying; Zhang, Can; Yu, Xintong; Cuthbertson, Andrew G. S.; Ali, Shaukat (Frontiers in Physiology, 2020)
Matrine, a naturally occurring heterocyclic compound, has been shown to enhance the pathogenicity of the entomopathogenic fungus Beauveria brongniartii against Spodoptera litura. In the current study, the biological impacts and synergism activities of these two agents on nutritional efficiency and antioxidant enzymes in S. litura were explored. Our results showed a high anti-feedant activity of B. brongniartii and matrine on S. litura. The S. litura larvae were unable to pupate and emerge when treated with combinations of matrine and B. brongniartii. Following on we measured the activities of five important antioxidant enzymes (SOD, POD, CAT, AChE, and GST) when treated with B. brongniartii SB010 (1 × 109 spores/mL), matrine (0.5 mg/mL), and B. brongniartii SB010 (1 × 109 spores/mL) + matrine (0.5 mg/mL). The results indicated the detoxification activity of the five enzymes in the fat body and hemolymph of S. litura when facing a combined B. brongniartii and matrine challenge. The activities of the enzymes were significantly lower than that of the control group 7 days post-treatment, indicating the inhibitory effect of the two xenobiotics. Matrine had better inhibition effects than B. brongniartii in a majority of the trials. The improved detoxification activity of the five enzymes may be the internal mechanism of synergism of matrine on B. brongniartii.